2012
DOI: 10.1097/ncm.0b013e3182529c05
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Minimally Invasive Technique on Return to Work and Narcotic Use Following Transforaminal Lumbar Inter-body Fusion

Abstract: There are limited data regarding time to return to work and duration of postoperative narcotic use following TLIF for low back pain. The available data appear to suggest that MIS TLIF may be associated with accelerated return to work and narcotic independence compared with open TLIF. Further analysis will be necessary to quantify the impact of MIS TLIF on workplace productivity and the indirect costs borne by patients and employers. Such information will be of value to case managers, disability managers, emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 35 publications
3
44
0
Order By: Relevance
“…Our study supports previously reported lower infection rates and intraoperative blood loss associated with MIS. 17,18,20,27,28,38 Combining traditional open deformity correction with MIS techniques is an alternative method of achieving the goals of deformity surgery. In our study the incidence of complications in the HYB group was between the rates for the MIS and OPEN subgroups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study supports previously reported lower infection rates and intraoperative blood loss associated with MIS. 17,18,20,27,28,38 Combining traditional open deformity correction with MIS techniques is an alternative method of achieving the goals of deformity surgery. In our study the incidence of complications in the HYB group was between the rates for the MIS and OPEN subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…17,18,20,24,27,28,36 Potential disadvantages may include limited sagittal correction. Complications of these increasingly applied procedures in the treatment of ASD must be examined, compared, and reported.…”
mentioning
confidence: 99%
“…13,20,32 These increased costs are mostly attributable to higher rates of complication, longer length of stay, more blood loss, and more postoperative services used compared with a minimally invasive approach. 3,13,19,[24][25][26]31 Additionally, studies have reported that a minimally invasive approach has been shown to be associated with faster narcotic independence, faster return to work after surgery, decreased pain, and decreased surgical time. 16,19,22,27 A review article by Parker et al found accelerated return to work and narcotic independence after minimally invasive TLIF compared with open TLIF.…”
Section: Discussionmentioning
confidence: 99%
“…3,13,19,[24][25][26]31 Additionally, studies have reported that a minimally invasive approach has been shown to be associated with faster narcotic independence, faster return to work after surgery, decreased pain, and decreased surgical time. 16,19,22,27 A review article by Parker et al found accelerated return to work and narcotic independence after minimally invasive TLIF compared with open TLIF. 19 However, few other 16 It is important to point out the larger cost difference associated with indirect costs in this study, which is greater than 3 times more than the savings in direct costs.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a tendency towards longer surgical time and greater exposure to radiation. 5,12,[15][16][17][18][19] …”
Section: Introductionmentioning
confidence: 99%